2016
DOI: 10.1177/0194599816637856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination of Tissue Eosinophilia in Patients with Chronic Rhinosinusitis and Nasal Polyposis

Abstract: Higher serum eosinophil levels may indicate more extensive mucosal disease as measured on CT scan. Neither serum nor tissue eosinophilia predicted disease severity in our retrospective analysis of CRSwNP patients, and serum eosinophil level did not serve as a marker of tissue eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 42 publications
(95 reference statements)
4
43
0
Order By: Relevance
“…The eosinophil count (70 cells/HPF) used in this study as the definition of ECRS is considerably higher than in earliest studies . On the other hand, it was reported that tissue eosinophilia did not predict disease severity in the retrospective analysis of CRSwNP patients . Therefore, there are no clear criteria for tissue eosinophilic infiltration for use in diagnosing ECRS.…”
Section: Discussionmentioning
confidence: 99%
“…The eosinophil count (70 cells/HPF) used in this study as the definition of ECRS is considerably higher than in earliest studies . On the other hand, it was reported that tissue eosinophilia did not predict disease severity in the retrospective analysis of CRSwNP patients . Therefore, there are no clear criteria for tissue eosinophilic infiltration for use in diagnosing ECRS.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that patients with more than 10% of eosinophils in their peripheral blood had a significantly higher disease recurrence rate than those with up to 10% of eosinophils. Gitomer et al . assessed a series of patients treated for CRSwNP from 2008 to 2010, and found that serum eosinophilia did not predict disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, eosinophilia was a reliable marker for severe and refractory sinusitis. Some studies focusing on the degree of tissue eosinophilia in chronic sinusitis and its bearing on the severity of CRS, which revealed the presence of peripheral eosinophilia in patients with sinusitis, indicated a high likelihood of extensive disease [9], but neither serum nor tissue eosinophilia predicted disease severity in CRSwNP patients [10, 11]. Sinonasal tissue eosinophilia is present in the majority of CRSwNP patients but it is currently more common in the West than in the East [12].…”
Section: Introductionmentioning
confidence: 99%